[(10-b:12):1+3]x6-24=0
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
Explicație pas cu pas:
[(10-b:12):1+3]x6-24=0
[(10-b:12):1+3]x6 = 24
(10-b:12):1+3 = 24 : 6 = 4
(10-b:12):1 = 4 - 3 = 1
10-b:12 = 1 x 1 = 1
b : 12 = 10 - 1 = 9
b = 12 x 9 = 108
lrssbotezatu:
multumesc!
Răspuns de
0
Răspuns:
[(10-b:12):1+3]x6-24=0
[(10-b:12):1+3]x6 =24
(10-b:12):1+3= 24 :6
(10-b:12):1+3 = 4
(10-b:12):1 = 4 - 3
(10-b:12):1 = 1
10-b:12=1×1
10-b:12= 1
10-b/12=1
10-1= b/12
9=b/12
b/12=9
b=9×12
b=108
Explicație pas cu pas:
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă